Clinical Contribution of Wrist and Hand Sonography: Pilot Study. (6th May 2018) - Tagliafico, Alberto; Bignotti, Bianca; Rossi, Federica; Rubino, Maurizio; Civani, Alessandro; Martinoli, Carlo
Abstract : Objectives: The purpose of this study was to evaluate the clinical contribution of wrist and hand sonography. Methods: This study was performed in a tertiary academic medical center. Institutional review board approval was obtained. Data collection was done retrospectively from January 2012 to December 2016 and prospectively from January 2017 to July 2017. The study included 112 consecutive patients (52 men and 60 women; mean age, 47 ± 16 years; range, 15–87 years). A total of 126 examinations were performed. All ultrasound examinations were done with high‐resolution probes with up‐to‐date protocols. The clinical contribution of wrist and hand sonography was assessed (ultrasound examinations contributive/noncontributive). Descriptive statistic and nonparametric tests were used. Results: In 96 of 126 (76%) examinations, sonography proved to be contributive, and in 30 of 126 (24%) examinations, sonography proved to be noncontributive. The contributive/noncontributive ratio was 3.2 (96/30). A total of 51 of 126 (40%) examinations were performed in patients with a history of previous trauma. Sonography proved to be significantly more contributive in a posttraumatic setting (chi‐square, 9.2; P  = .0023). Conclusion: Wrist and hand sonography significantly influences the diagnostic and therapeutic path, especially in a posttraumatic setting.